A first case of ductal adenocarcinoma of the prostate having characteristics of neuroendocrine phenotype with PTEN, RB1 and TP53 alterations - Hiroaki Kobayashi; Takeo Kosaka; Kohei Nakamura; Kazunori Shojo; Hiroshi Hongo; Shuji Mikami; Hiroshi Nishihara; Mototsugu Oya (BMC, 2021)
Abstract Background Ductal adenocarcinoma and neuroendocrine cancer are rare subtypes of prostate cancer with poor prognosis and limited therapeutic options. We present the first case of ductal adenocarcinoma having a neuroendocrine phenotype. Case presentation A 63-year-old man presented with gross hematuria and urinary retention, and his serum prostate-specific antigen level was 4.58 ng/mL. We performed transurethral resection of the prostate, and the diagnosis was ductal adenocarcinoma with a Gleason score of 5 + 4 for acinar adenocarcinoma. Magnetic resonance imaging showed local invasion of left lobe of the prostate and bone metastasis of the left trochanteric section of the femur. Multidisciplinary treatments such as androgen deprivation therapy, chemoradiation therapy, and surgery for metastatic lesions have led to long-term survival. Since next-generation sequencing revealed PTEN and RB1 co-loss and TP53 mutations, we re-evaluated the immunohistochemistry and he was found to be positive for synaptophysin. Conclusions This is the first Japanese case of ductal adenocarcinoma with a neuroendocrine phenotype. Genetic analysis may help not only guide the therapeutic strategies, but also sometimes with the diagnosis.